A Brief Overview on Experimental Zoology: Advancements, Problems and Future Prospects - Andrei Alimov (Research Aspects in Biological Science Vol. 2, 2022)
Advances in cell and molecular biology have provided entirely new animal models, which are widely used in solving both applied and scientific problems. The wildest dreams in this area became a reality in the late 20th - early 21st century. This review summarizes the most significant achievements in this field, including the generation of genetically modified fish, inbred strains and humanized mouse models.